Degloving injuries with versus without underlying fracture in a sub-Saharan African tertiary hospital: a prospective observational study - Lekuya, Hervé Monka; Alenyo, Rose; Bangirana, Alexander; Mbiine, Ronald; Galukande, Moses (Journal of orthopaedic surgery and research, 2018)
Degloving injuries are surgical conditions in which an extensive portion of skin and subcutaneous tissue is detached from the underlying fasciae, muscles, or bone surface. Frequently, there is an association of fracture underlying the degloved area. We aimed to compare the short-term outcomes of degloving injuries with and without underlying fracture.
Keywords: Degloving, Soft tissue injury, Morel-Lavallé lesion, ISS, Trauma, Fracture, Debridement, Infection